Implications of Prenatal Exposure to the Spring 2011 Alabama and Missouri Tornadoes on Birth Outcomes. (20th June 2018) - Christopher, Kenneth E.; Kitsantas, Panagiota; Spooner, Kiara K.; Robare, Joseph F.; Hanfling, Dan
ABSTRACT: Objective: Despite emerging evidence of the detrimental effects of natural disasters on maternal and child health, little is known about exposure to tornadoes during the prenatal period and its impact on birth outcomes. We examined the relationship between prenatal exposure to the spring 2011 tornado outbreak in Alabama and Joplin (Missouri) and adverse birth outcomes. Methods: We conducted a retrospective, cross-sectional cohort study using the 2010-2012 linked infant births and deaths data set from the National Center for Health Statistics for tornado-affected counties in Alabama (n=126, 453) and Missouri (Joplin, n=6, 897). Chi-square and logistic regression analyses were performed to estimate associations between prenatal exposure to tornadoes and birth outcomes. Results: Prenatal exposure to the tornado incidents did not influence birth weight outcomes. Women exposed to Alabama tornadoes were less likely to have a preterm birth compared to unexposed mothers (OR: 0.93, 95% CI: 0.91, 0.96). Preterm births among Joplin-tornado exposed mothers were slightly higher (13%) compared with unexposed mothers (11.2%). Exposed mothers from Joplin were also more likely to have a cesarean section compared to their counterparts (OR: 1.14, 95% CI: 1.02, 1.26). Conclusions: We found no association between tornado exposure and adverse birth weight and infant mortality rates. Our findings suggest that prenatal exposure can amplify the odds for a cesarean section. ( Disaster Med Public Health Preparedness. 2019;13:279–286)